THE INFLUENCE OF PRODUCT QUALITY AND SERVICE QUALITY ON CONSUMER SATISFACTION: A STUDY ON SURRATI PERFUME AT PT. AMANAH DIKI SETIAWAN, DEPOK - Siti Sopiyatul Munawaroh; Hartanto Halim; Eman Sulaiman (PT. Berkah Digital Teknologi, 2025)
Purpose: The purpose of this research is to determine the influence of Product Quality and Service Quality on Consumer Satisfaction for Surrati perfume products at PT. Amanah Diki Setiawan, Depok City. Research Methodology: This study employs a quantitative research method, utilizing Slovin's sampling technique. The population comprises 4,937 consumers of Surrati perfume, with a sample size of 98 consumers. Results: Partial testing indicates that Product Quality significantly affects Consumer Satisfaction, with a calculated t-value of 6.604 (t_hitung > t_tabel; 6.604 > 1.988) and a significance value of 0.000 (< 0.05), leading to the acceptance of the alternative hypothesis (Ha). Product Quality accounts for 46.7% of the positive relationship with Consumer Satisfaction. In terms of Service Quality, the t-value is 2.289 (t_hitung > t_tabel; 2.289 > 1.988) with a significance value of 0.024 (< 0.05), thus also supporting Ha, indicating a 2.50% positive impact on Consumer Satisfaction. Simultaneous testing reveals an F-value of 46.619 (F_hitung > F_tabel; 46.619 > 3.09) and a significance value of 0.000 (< 0.05), confirming that both Product Quality and Service Quality together influence Consumer Satisfaction by 47.9%. Limitations: The study is limited to a single company and product line, which may affect the generalizability of the findings to other contexts. Contribution: This research contributes to the understanding of the relationship between product and service quality and consumer satisfaction, providing insights that can help improve marketing strategies for Surrati perfume products.